DEVELOPMENT AND VALIDATION OF LIQUID CHROMATOGRAPHIC METHOD FOR ESTIMATION OF ESCITALOPRAM OXALATE IN TABLET DOSAGE FORMS - SYAMA SUNDAR.B; SUNEETHA.A (International Journal of Pharma and Bio Sciences, 2010)
A simple, specific, accurate and precise RP-HPLC method was developed and validated for the determination of escitalopram oxalate in tablet dosage forms. A hypersil BDS C8, 5- column having 250x4.6mm internal diameter in isocratic mode with mobile phase containing methanol: disodium hydrogen phosphate: acetonitrile (28:44:28v/v, pH 7.0±0.05) was used. The flow rate was 1.5ml/min and effluents were monitored at 226nm. The retention time of escitalopram oxalate was 8.45 min. The linearity range is 250-1500-g/ml with coefficient of correlation 0.9999. The method was validated in terms of accuracy, precision, repeatability. The percentage recovery for escitalopram oxalate was found to be 99.0%. The proposed method was successfully applied for quantitative determination of escitalopram oxalate in single dosage form for routine analysis.